Strategi dan Model Omnibus Law dalam Penataan Regulasi - Bambang Sri Hartono; Ayon Dini Yanto; Heris Suhendar (Program Studi Hukum Keluarga Islam, 2021)
Formation of the Omnibus Law, There are at least two basic reasons for the name many overlapping regulations and many regulations that are allegedly hampering investment so that the establishment of the Omnibus Law is expected to be able to overcome these two problems. The purpose of writing the article is to explain Omnibus Law in the system in Indonesia, the strategy and model of Omnibus Law in structuring regulations in Indonesia, and the challenges of Omnibus Law in structuring regulations. This article can be categorized as a type of normative juridical research using a qualitative approach. The source of data in writing this article uses secondary data consisting of primary legal materials in the form of Omnibus Law, secondary legal materials in the form of journal articles, law books, magazines and so on, and tertiary legal materials in the form of legal dictionaries, legal encyclopedias and others. . The results of the study indicate that the regulatory structuring strategy through the Omnibus Law can be carried out by establishing the basic and legal politics of the Omnibus Law, absorbing aspirations, coordinating with the regions, acceleration, transparency and accountability. The regulatory arrangement model through the Omnibus Law can be done with the regulation formation model, namely IRR. Meanwhile, the challenges of the Omnibus Law in structuring regulations are in the form of current and future challenges. In the formation of the Omnibus Law, the community is expected to participate in conducting supervision.Pembentukan Omnibus Law saat ini setidaknya ada dua alasan mendasar yakni banyak regulasi yang tumpang tindih dan banyak regulasi yang disinyalir menghambat investasi, sehingga dengan dibentuknya Omnibus Law nantinya diharapkan dapat mengatasi kedua permasalahan tersebut. Tujuan penulisan artikel yaitu menjelaskan tentang strategi dan model Omnibus Law dalam penataan regulasi di Indonesia, dan tantangan Omnibus Law dalam penataan regulasi. Artikel ini dapat dikategorisasikan sebagai jenis penelitian yuridis normatif dengan menggunakan pendekatan kualitatif. Sumber data dalam penulisan artikel ini menggunakan data sekunder yang terdiri dari bahan hukum primer berupa Omnibus Law, bahan hukum sekunder berupa artikel jurnal, buku-buku hukum, majalah dan lain sebagainya, dan bahan hukum tersier berupa kamus hukum, ensiklopedi hukum dan lain-lain. Hasil penelitian menunjukkan bahwa Strategi penataan regulasi melalui Omnibus Law dapat dilakukan dengan pembentukan dasar dan politik hukum Omnibus Law, penyerapan aspirasi, koordinasi dengan daerah, akselerasi, transparansi dan akuntabilitas. Model penataan regulasi melalui Omnibus Law dapat dilakukan dengan model pembentukan regulasi yaitu IRR. Sedangkan tantangan Omnibus Law dalam penataan regulasi berupa tantangan saat ini dan masa mendatang. Dalam pembentukan Omnibus Law masyarakat diharapkan turut serta dalam melakukan pengawasan.